2019
DOI: 10.1016/j.polymdegradstab.2019.108947
|View full text |Cite
|
Sign up to set email alerts
|

Physical ageing of epoxy in a wet environment: Coupling between plasticization and physical ageing

Abstract: This paper shows how physical ageing and plasticization processes are coupled in an amine-based epoxy. The study combines several ageing conditions including thermal ageing in the dry state (from 40 to 60 °C), ageing in a humid environment (RH 50% and RH 75%) as well as immersion in seawater at several temperatures from 15 to 40 °C. First results are presented to highlight that the two processes (physical ageing and plasticization) both occur when the epoxy is immersed in water. A step-by-step approach is then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…This study focused on the environmental aging resistance of the epoxy resin matrix, including long-term exposure to humidity, temperature, water/salt or alkali solution, etc. It was found that the property evolution of the resin matrix was mainly dependent on the water absorption, and the effect of water molecules on chemical reactions included the destruction of the original group (such as the crosslinking fracture of the molecular segment) and the generation of microcracks and micropores from the swelling of the resin matrix, which had complex effects on the macro mechanical properties of the resin [9][10][11]. Therefore, the evaluation of structures and properties evolution of epoxy resin exposed to the above service environments is significant to provide rapid laboratory testing and long-life evaluation of epoxy resin for engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused on the environmental aging resistance of the epoxy resin matrix, including long-term exposure to humidity, temperature, water/salt or alkali solution, etc. It was found that the property evolution of the resin matrix was mainly dependent on the water absorption, and the effect of water molecules on chemical reactions included the destruction of the original group (such as the crosslinking fracture of the molecular segment) and the generation of microcracks and micropores from the swelling of the resin matrix, which had complex effects on the macro mechanical properties of the resin [9][10][11]. Therefore, the evaluation of structures and properties evolution of epoxy resin exposed to the above service environments is significant to provide rapid laboratory testing and long-life evaluation of epoxy resin for engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…At lower temperatures, these changes will take longer. Previous work on this same epoxy resin without fiber reinforcement [35] showed such an embrittlement with physical ageing, with faster property changes at closer to Tg temperatures. This is a reversible process; complete recovery of initial properties was noted after rejuvenation, a thermal treatment above Tg.…”
Section: Influence Of An Accelerated Wet Ageing Protocol On Mixed Mode Failure Criteriamentioning
confidence: 56%
“…Based on these values, water is found more detrimental to than temperature. According to Guen-Geffroy et al [ 28 ] and Yang et al [ 14 ], when epoxy resin is aged in a wet environment, the decrease in its can be primarily associated with plasticization. In general, these values are consistent with the values from DSC, and the values are the closest ones.…”
Section: Resultsmentioning
confidence: 99%